Civil society and modern politics - Saha, Dipali (Ed.) (Delhi, 2004)
This Book Is A Critical Analysis Of Conflict And Compromise Between Civil Society And Modern Politics. Theory Of Civil Society And Its Relation With Modern Politics Has Been Drawn From Two Main Sources: First, The Writings Of Kant, Hegel, Feuerbach, Marx And, More Recently, Weber, Schmitt, Benjamin, Adorno And Arendt; And Second, An Analysis Of Actual Attempts To Sustain It In A Public Sphere, And Political Recognition In Contemporary World. Here, It Will Attempt To Answer These Questions With A Brief Recapitulation Of The Relevance Of Kant, Hegel, Marx, Benjamin, Arendt And Other Modern Thinkers For An Understanding Of The Relationship Between Civil Society And Modern Politics.
Keywords: Civil society